The Wolves in Sheep's Clothing: How Russia's Internet Research Agency Tweets Appeared in U.S. News as Vox Populi. (April 2020) - Lukito, Josephine; Suk, Jiyoun; Zhang, Yini; Doroshenko, Larissa; Kim, Sang Jung; Su, Min-Hsin; Xia, Yiping; Freelon, Deen; Wells, Chris
The Russian-sponsored Internet Research Agency's (IRA) use of social media to influence U.S. political discourse is undoubtedly troubling. However, scholarly attention has focused on social media, overlooking the role that news media within the country played in amplifying false, foreign messages. In this article, we examine articles in the U.S. news media system that quoted IRA tweets through the lens of changing journalism practices in the hybrid media system, focusing specifically on news gatekeepers' use of tweets as vox populi. We find that a majority of the IRA tweets embedded in the news were vox populi. That is, IRA tweets were quoted (1) for their opinion, (2) as coming from everyday Twitter users, and (3) with a collection of other tweets holistically representing public sentiment. These findings raise concerns about how modern gatekeeping practices, transformed due to the hybrid media system, may also unintentionally let in unwanted disinformation from malicious actors.